2019
DOI: 10.20886/jphh.2019.37.1.1-12
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kadar Air Terhadap Kualitas Pelet Kayu Dari Serbuk Gergajian Kayu Jabon Dan Ketapang

Abstract: In the last few years, wood pellet demand has increased globally for residential purposes. In term of standard quality, wood pellet for residential purposes are tighter than industrial purposes. The wood pellet quality parameters are moisture changes in biomass, impacts on bulk density, and mechanical durability. This paper analyzes the effect of biomass moisture content (MC) into the quality of wood pellet made from jabon and ketapang sawdust to meet quality standard of ISO 17225-2. The pellet was grouped int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Lab-based calorific value tests show that variation A has the highest value, while variation K has the lowest, primarily due to the lower moisture content in variation A, leading to a higher calorific value. An augmented calorific value has the potential to expedite thermal release during fuel combustion, subsequently conserving fuel consumption [13]. Although all variations adhere solely to class 3 quality standards, variation A nearly satisfies the stipulated criteria for class 2 quality classification.…”
Section: Calorific Valuementioning
confidence: 98%
See 1 more Smart Citation
“…Lab-based calorific value tests show that variation A has the highest value, while variation K has the lowest, primarily due to the lower moisture content in variation A, leading to a higher calorific value. An augmented calorific value has the potential to expedite thermal release during fuel combustion, subsequently conserving fuel consumption [13]. Although all variations adhere solely to class 3 quality standards, variation A nearly satisfies the stipulated criteria for class 2 quality classification.…”
Section: Calorific Valuementioning
confidence: 98%
“…The K variation exhibits the most substantial volatile content, specifically quantifying at 69.33 ± 6.66%. Elevated levels of volatility can pose health risks due to the potential escalation of carbon monoxide (CO) gas concentrations [13]. Conversely, variations A and D display the least volatile content, both registering an equivalent value of 65.00 ± 1%.…”
Section: Volatile Contentmentioning
confidence: 99%
“…The MC will greatly affect the characteristics of the betung bamboo pellets. MC that is too high will cause the pellets to be susceptible to microorganisms and fungi so that the pellets will easily expand in the distribution and storage process (Lestari et al, 2019).…”
Section: Moisture Contentmentioning
confidence: 99%
“…On the basis of the study results, it can be concluded that the addition of the garden waste mixture in the pellets can affect the decrease in density. The garden water content is relatively smaller so that when the pellet is pressed, the particles become easily pressed, which results in reduced (Lestari et al, 2019) conducted density testing of sawdust pellets for Jabon and Ketapang wood, producing an average density value ranging from 976-1072 kg/m 3 . Compared to this study, the average density value was higher, which shows better pellet quality.…”
Section: Densitymentioning
confidence: 99%